Comportamiento productivo del cultivo de sandía royal charleston (Citrullus vulgaris.) con diferentes distancias de siembra. - Moreira Peñafiel, Daniel Ernesto (2010)
This investigation one carries out in the Agricultural "Property Julia María", property of Mr. Daniel Moreira Solórzano, located in the Km. 20 of the road The Esperanza the Vergel, Canton Valencia, with the geographical coordinates 79º 28' 00 '' W of longitude west and 0º 55' 00 '' of south latitude, to a height of 120 m on the level of the sea; one had as objective to evaluate the “productive Behavior of the cultivation of simple royal charleston (citrullus vulgaris.) with different siembra distances” The investigation had a duration of 120 days in the field phase. For it was developed it an Experimental Design in Blocks Totally at random (DBCA) with four treatments five repetitions and eight experimental units, to determine the statistical differences of the stocking, you applies the test of multiple ranges of Tukey (P ≥0.05) of probability, according to the statistical position 40 plants were used by each treatment, forming 20 parcels of 8 experimental units each a, with a total of 160 plants, where floración time, crop time, was evaluated I number of fruits for plant, weight of the fruit, diameter of the fruit and longitude of the fruit. In the floración time there were not differences, this it was presented to the 29 days obtaining their full floración to the 37 days in all the treatments, this result was given with normality in the vegetative stage of the cultivation. In what refers to the number of fruits for plant there were not significant statistical differences among the treatments, being the best treatment the T3 5mx1m, presenting an average of 3.00 fruits for plant with a density of siembra of 2000 plants for hectare and a production for hectare of 5333 fruits considering it good, followed by the treatments T2 4mx1m, with 2.20 fruits for plant with a density of siembra of 2500 plants for hectare with production for hectare of 4889 fruits and T4 6mx1m, with 1.95 fruits for plant, and a production for hectare of 2889 fruits, density of siembra of 1666 plants for hectare. Being in the range from 3 to 4 fruits for plant of the production. The smallest production in number of fruits obtained it the T1 3mx1m, with 1.30 fruits for plant with a density of siembra of 3333 plants for hectare. In the variable weight of the fruit it presented significant statistical differences, the treatment that he/she obtained the best result was the T3 D. 5mx1m (D.H.) with an average of 20.10 kg for fruit with a production for hectare of 35.73 tons; continued by the treatments T2 D. 4mx1m (D.H.) with 15.35 Kg for fruit production for hectare of 34.11 tons; and T4 D. 6mx1m (D.H.) with 15.10 kg. for fruit and a production for hectare of 22.37 tons. These three treatments are inside the ranges from 20 to 40 tons for hectare. The smallest production obtained it the T1 D. 3mx1m (D.H.) with 6.65 Kg for fruit and a production for hectare of 19.70 tons. The best result for the diameter of the fruit was for the T3 D. 5mx1m (D.H.) with an average of 25.00 diameter cm. This inside the range of 25 to 26 cm. of diameter. The biggest longitude in the fruit obtained it the treatment T3 D. 5mx1m (D.H.) with an average of 62.90 cm. of longitude, followed by the T2 D. 4mx1m (D.H.) with an average of 52.00cm. of longitude. In relation to the time it harvests there were not differences among the treatments this he/she was carried out to the 105 days after the siembra in all the treatments. The smallest cost presented it the treatment of smaller area in m² T1 3mx1m, 67.5 m² with $58,10 USD with low profitability of -1,55 % producing 26 fruits for treatment and the biggest profitability registered it the treatment T3 5mx1m, with an area of 112.5 m² producing 60 fruits for treatment, where he/she obtained the biggest profitability 90,75% with an investment of $ 69,20 for the treatment.